Faktor Eksternal yang Mempengaruhi Perkembangan Anak Usia Dini - Maghfhirah, Siti; Latipah, Eva (AL-HANIF: Jurnal Pendidikan Anak dan Parenting, 2021)
To understand early childhood development, parents or professional teachers must first understand the conceptual meaning of early childhood development, including the factors that influence development. Thus, it is possible to plan, identify and know the steps that need to be taken to help your child's early childhood development develop optimally. One of the factors that influence the development of early childhood is external factors. Factors originating from environmental causes (especially family: related to the role of parents), the process of maturation of the environment in children is very important for parents to know. Knowing these external factors is expected to help the child's development process properly and appropriately.